The Optimization of Vapor Compression Type for Desalination of Seawater Using the DFMA Method - Irfan Santosa; Aditya Firdaus; Royan Hidayat; Rusnoto Rusnoto; Agus Wibowo; Fathan Mubina Dewadi (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2022)
The design of vapor compression type distillation using the design for manufacture and assembly (DFMA) method was discussed in this article. The efficacy of seawater desalination is the primary source of non-conventional fresh water in a large number of countries around the world. The distillation process can satisfy the demands for high-quality fresh water by utilizing seawater. DFMA is a technique for product development and improvement that could be used to simplify the manufacturing process and reduce assembly costs. This research focuses on creating an effective vapor compression-type desalination device. The DFMA method is used in this reverse engineering study. According to the findings of this study, the total assembly time of 22 components was 7932 seconds. Compared to the previous process, processing time efficiency increased by 4.1 %.